Sonogram Pemeriksaan Kebuntingan Dini pada Kambing Kacang (Capra hircus) - Santoso Santoso; Amrozi Amrozi; Bambang Purwantara; Herdis Herdis (Jurnal Sain Veteriner, 2016)
This study was conducted to determine the earliest day of pregnancy diagnosis in kacang goat using transrectal ultrasonography. The goat were synchronized by using prostaglandin in the luteal phase. Pregnancy was determined by isoechogenic visualization surrounded by hypoechogenic. Early pregnancy was detected on days 20 of embryonic vesicle diameter 1.2±0.1 cm. Fetus was detected on days 22 with a long gestation fetus 0.4±0.1 cm. Average increase until days 30 pregnancy was 0.19 ± 0.1 cm per day. Development of fetus was followed by an increasing the diameter and thickness of uterus. The diameter of uterus increased from days 14 (0.8 ± 0.3 cm) until days 30 (3.6 ± 0.2 cm), and thickness of uterus increased from days 14 (0.4 ± 0, 2 cm) until days 30 (1.8 ± 0.2 cm). It could be concluded that the earliest pregnancy diagnosis showed positive sign on days 20 and fetus was earliest observed on days 22.